MiR-204-5p regulates HUVEC cell inflammation and apoptosis by targeting P4HB: miR-204-5p regulates HUVEC inflammation - Chen, Jun; Zhang, Kaixin; Yang, Yi; Wu, Jianqiang (Cellular and Molecular Biology, 2023)
The purpose of this study arose to investigate the mechanism of miR-204-5p targeting P4HB to regulate inflammation and apoptosis in HUVEC cells. Serum specimens were obtained from lower extremity DVT patients and healthy subjects. Targetscan predicted P4HB as a target gene for miR-204-5p. A dual luciferase reporter assay was conducted to determine the modulating effect of miR-204-5p on P4HB. qRT-PCR was used to detect miR-204-5p and P4HB expression. Established CoCl2-induced hypoxia/ischemia model of HUVEC, transfected with miR-204-5p mimics and pcDNA3. 1-P4HB. CCK-8 assay for cell viability. Apoptosis was assayed by flow cytometry, western blot and western blot. Immunofluorescence and ELISA were carried out to detect ROS, MDA, SOD, LDH, GSH-px, TNF-α, IL-1β and IL-6 expression. miR-204-5p was reduced markedly in the sera of DVT patients. miR-204-5p negatively regulated P4HB. P4HB expression was raised in the sera of DVT patients. Exposure to CoCl2 decreased miR-204-5p expression and increased P4HB in HUVEC. Over-expressed miR-204-5p effectively increased cell viability and inhibited apoptosis; its effect was counteracted by continued overexpression of P4HB. In addition, miR- 204-5p mimics clearly reduced CoCl2-induced ROS and inflammation, and pcDNA3. 1-P4HB acted counteractively. miR-204-5p may inhibit HUVEC proliferation, ROS generation and cellular inflammation through negative regulation of P4HB. miR-204-5p promises to become a potential target for DVT therapy.